How to recognize and manage psychosomatic pain in the pediatric emergency department - Giorgio Cozzi; Annunziata Lucarelli; Fabio Borrometi; Ilaria Corsini; Eva Passone; Sara Pusceddu; Giuliana Morabito; Egidio Barbi; Franca Benini (BMC, 2021)
Abstract Aim Children and adolescents affected by somatization and somatic symptom disorder commonly refer to emergency services. Due to the absence of specific guidelines for the emergency setting and to a possible lack of knowledge, these patients are at risk of being unrecognized and mismanaged. This study aims at proposing a clinical practice to approach and manage these patients and their families in the emergency setting. Methods This manuscript derived from the work of a research group of italian pediatric emergency physicians and anesthesiologists, with an expertise in pain management, members of the PIPER group. The research group reviewed the literature about psychosomatic pain and somatic symptom disorder and developed a clinical practice specific for the pediatric emergency setting. Results The manuscript provides information about the main clinical features shared by patients with psychosomatic pain and about current diagnostic criteria and appropriate management in the emergency setting. Furthermore, it highlights the possible pitfalls in which the emergency physician may run into dealing with these patients. Conclusion This clinical practice should be seen as a starting point toward a better understanding of patients with psychosomatic pain and a standardization of care in the pediatric emergency setting.